Single vesicle analysis of aqueous humor in pediatric ocular diseases reveals eye specific CD63‐dominant subpopulations. Issue 4 (20th April 2022) - Peng, Chen‐Ching; Im, Deborah; Sirivolu, Shreya; Reiser, Bibiana; Nagiel, Aaron; Neviani, Paolo; Xu, Liya; Berry, Jesse L.
Abstract: Aqueous humor (AH), the clear fluid in front of the eye, maintains the pressure and vitality of ocular tissues. This fluid is accessible via the clear cornea which enables use of AH as a liquid biopsy source of biomarkers for intraocular disease. Extracellular vesicles are detectable in the AH and small extracellular vesicles (sEVs) are present in the AH from adults. However, EVs in AH from pediatric eyes in vivo have never previously been explored. We know very little about the heterogeneity of AH EV populations in ocular disease. Twenty‐seven processing‐free AH samples from 19 patients across four different pediatric ocular diseases were subjected to Nanoparticle Tracking Analysis (NTA) and Single Particle‐Interferometric Reflectance Imaging Sensor (SP‐IRIS) analysis. NTA demonstrated the concentration of AH EV/EPs is 3.11 × 10 9 –1.38 × 10 10 particles/ml; the majority sized 76.8–103 nm. SP‐IRIS revealed distinct patterns of tetraspanin expression of AH sEVs. An enriched mono‐CD63+ sEV subpopulation identified in AH indicates this is a potential AH‐specific biomarker. In the setting of retinoblastoma there was a more heterogeneous population of sEVs which normalized with treatment. This suggests a potential clinical application of direct measurement of sEV subpopulations in AH samples to monitor successful tumor response to therapy.